A Blended Learning Module on the Writing Academic Purpose Course (A Research and Development Approach) - Eny Maulita Purnama Sari; Nurul Aini (Center of Language and Cultural Studies [CLCS], 2019)
This study aimed to determine the effectiveness of the module based on blended learning model in â€˜Writing Academic Purposeâ€ course, to evaluate the validity of the module based on the assessment by the Context, linguists and media experts used validation sheets. The module was developed using Research and Development Approach (R&D). the outputs of this research was an blended learning module of â€œWriting Academic Purposeâ€. The module was implemented using the e-learning system of UNU Lampung. The subject of this research was the blended learning module that implemented to the English Department students. The object of the research were the content of the module. The module is declared valid from the validation by validators, the module could improve the studentsâ€™ reasoning and creativity, the moduleâ€™s effectiveness is achieved in this study.